WOMAN, A UNIVERSAL CONCEPT? : THE IDENTITY OF “WOMAN” AS A MECHANISM OF SYMBOLIC VIOLENCE IN HEGEMONIC FEMINISM - Almeida Burite, Haylana (Revista Gênero e Interdisciplinaridade, 2022)
This academic essay based on a literature review aims to demonstrate the correlation between the universalization of the subject “woman” and the maintenance of non-emancipatory practices. It is a critique of social immobility and the reinforcement of patriarchy from the duality maintained between mind and body in hegemonic feminism. Therefore, the perspectives of post-feminists were analyzed, in the view of the American post-structuralist philosopher Judith Butler; and black feminism, in the conception of the African-American sociologist Patricia Hill Collins.